2019
DOI: 10.1371/journal.pone.0219924
|View full text |Cite
|
Sign up to set email alerts
|

Language processing skills linked to FMR1 variation: A study of gaze-language coordination during rapid automatized naming among women with the FMR1 premutation

Abstract: The FMR1 premutation (PM) is relatively common in the general population. Evidence suggests that PM carriers may exhibit subtle differences in specific cognitive and language abilities. This study examined potential mechanisms underlying such differences through the study of gaze and language coordination during a language processing task (rapid automatized naming; RAN) among female carriers of the FMR1 PM. RAN taps a complex set of underlying neuropsychological me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 108 publications
0
19
0
Order By: Relevance
“…For example, Mosconi et al (2010) found that firstdegree relatives of individuals with ASD demonstrated ocular-motor differences such as minor inaccuracies in direction of eye movement and subtly reduced inhibition of eye movements. Differences in eye-voice coordination have also been observed in ASD and among parents in nonsocial, rapid automatized naming tasks requiring fluid scanning and naming of colors, objects, letters, and numbers (Nayar et al 2018). Of note, similar differences in eye-voice coordination have been noted in carriers of the FMR1 premutation (Nayar et al 2019).…”
Section: Origins Of Social Communication Differences In Asd and Firstmentioning
confidence: 77%
See 2 more Smart Citations
“…For example, Mosconi et al (2010) found that firstdegree relatives of individuals with ASD demonstrated ocular-motor differences such as minor inaccuracies in direction of eye movement and subtly reduced inhibition of eye movements. Differences in eye-voice coordination have also been observed in ASD and among parents in nonsocial, rapid automatized naming tasks requiring fluid scanning and naming of colors, objects, letters, and numbers (Nayar et al 2018). Of note, similar differences in eye-voice coordination have been noted in carriers of the FMR1 premutation (Nayar et al 2019).…”
Section: Origins Of Social Communication Differences In Asd and Firstmentioning
confidence: 77%
“…Differences in eye-voice coordination have also been observed in ASD and among parents in nonsocial, rapid automatized naming tasks requiring fluid scanning and naming of colors, objects, letters, and numbers (Nayar et al 2018). Of note, similar differences in eye-voice coordination have been noted in carriers of the FMR1 premutation (Nayar et al 2019). Full mutations of the FMR1 gene cause fragile X syndrome, the most common inherited cause of intellectual disability and also the monogenic disorder most frequently associated with ASD (e.g., Zafeiriou et al 2013).…”
Section: Origins Of Social Communication Differences In Asd and Firstmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, compared to mothers of children with ASD who were considered to have similar parental experiences to the PM mothers of children with FXS, the latter group had higher scores in verbal dysfluency and impaired self-monitoring [ 92 ]. Furthermore, in a study by Nayar and colleagues, they examined language processing skills in 46 females with the PM and 56 controls and they found a pattern of inefficient language processing among the females with the PM [ 93 ]. In individuals with FXTAS, it is necessary to address cognitive impairment and implement early intervention since impaired information processing speed, response inhibition, and working memory could interfere with their mobility [ 94 ].…”
Section: Clinical Presentation Of Fxtasmentioning
confidence: 99%
“…Differences in executive skills have also been reported, including working memory, inhibitory control, and processing speed ( Wang et al, 2013 ; Shelton et al, 2014 , 2015 , 2016 ). Subclinical phenotypic differences have also been documented in social cognition ( Cornish et al, 2005 ; Losh et al, 2008 ), language processing ( Nayar et al, 2019 ), and social language use ( Losh et al, 2012 ; Klusek et al, 2016 ) in women with the PM. Manifestation of the PM phenotype is thought to be in part related to molecular-genetic differences including levels of FMRP and CGG repeat length ( Wheeler et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%